Social Responsibility from the Qur’anic Perspective: Its Relevance to the Management of Islamic Public Institutions - Sandika, Arvan; Mahmud , Hamidullah (The Future of Education Journal, 2025)
This study aims to examine the concept of social responsibility from the perspective of the Qur’an and its relevance to the governance of Islamic public institutions. The background of this study is grounded in the importance of the principle of mas’uliyyah (responsibility) as a moral and social foundation for human interactions with God, fellow human beings, the environment, and the self. The research employs a qualitative literature review approach, involving descriptive and comparative analyses of Qur’anic verses and interpretations by classical and contemporary Islamic scholars. The findings indicate that social responsibility in Islam encompasses both individual and communal obligations based on the values of amanah (trustworthiness), justice, ihsan (excellence), and socio-spiritual balance. The application of these values in the management of Islamic public institutions can enhance accountability, social justice, and organizational performance through ethical leadership and a strong commitment to community welfare. This study emphasizes that the integration of Qur’anic principles into public governance constitutes an essential foundation for character development and sustainable governance in Islamic institutions.